Chromosome Painting in Gymnotus carapo “Catalão” (Gymnotiformes, Teleostei): Dynamics of Chromosomal Rearrangements in Cryptic Species - Machado, Milla de Andrade; da Silva, Maelin; Feldberg, Eliana; O’Brien, Patricia Caroline Mary; Ferguson-Smith, Malcolm Andrew; Pieczarka, Julio Cesar; Nagamachi, Cleusa Yoshiko (Frontiers in Genetics, 2022)
The genus Gymnotus is a large monophyletic group of freshwater weakly-electric fishes, with wide distribution in Central and South America. It has 46 valid species divided into six subgenera (Gymnotus, Tijax, Tigre, Lamontianus, Tigrinus and Pantherus) with large chromosome plasticity and diploid numbers (2n) ranging from 34 to 54. Within this rich diversity, there is controversy about whether Gymnotus (Gymnotus) carapo species is a single widespread species or a complex of cryptic species. Cytogenetic studies show different diploid numbers for G. carapo species, ranging from 40 to 54 chromosomes with varied karyotypes found even between populations sharing the same 2n. Whole chromosome painting has been used in studies on fish species and recently has been used for tracking the chromosomal evolution of Gymnotus and assisting in its cytotaxonomy. Comparative genomic mapping using chromosome painting has shown more complex rearrangements in Gymnotus carapo than shown in previous studies by classical cytogenetics. These studies demonstrate that multiple chromosome pairs are involved in its chromosomal reorganization, suggesting the presence of a complex of cryptic species due to a post zygotic barrier. In the present study, metaphase chromosomes of G. carapo occidentalis “catalão” (GCC, 2n=40, 30m/sm+10st/a) from the Catalão Lake, Amazonas, Brazil, were hybridized with whole chromosome probes derived from the chromosomes of G. carapo (GCA, 2n=42, 30m/sm+12st/a). The results reveal chromosome rearrangements and a high number of repetitive DNA sites. Of the 12 pairs of G. carapo chromosomes that could be individually identified (GCA 1–3, 6, 7, 9, 14, 16 and 18–21), 8 pairs (GCA 1, 2, 6, 7, 9, 14, 20, 21) had homeology conserved in GCC. Of the GCA pairs that are grouped (GCA [4,8], [5,17], [10,11] and [12,13,15]), most kept the number of signals in GCC (GCA [5,17], [10,11] and [12,13,15]). The remaining chromosomes are rearranged in the GCC karyotype. Analysis of both populations of the G. carapo cytotypes shows extensive karyotype reorganization. Along with previous studies, this suggests that the different cytotypes analyzed here may represent different species and supports the hypothesis that G. carapo is not a single widespread species, but a group of cryptic species.